Mixed integer programming to minimize train delays / Nor Atiyah Mohd Zulkifli and Noraini Noordin - Mohd Zulkifli, Nor Atiyah; Noordin, Noraini (Universiti Teknologi MARA, Perlis, 2016)
Keretapi Tanah Melayu (KTM) train services are more preferred over other transportations due to easy public access to train stations in Malaysia. However, train arrival time has increased with time delays experienced by most customers with KTM Komuter services. The current study aimed to minimize total delay time of trains. Having exhibited similarities to previous works in this area, this study has chosen to adapt the Mixed Integer Programming (MIP) method to the Padang Besar (PB)-Sungai Petani (SP) KTM Komuter service routes. Included as decision variables were start and end time of rescheduled event as well as total delay from the rescheduled event. Primary data needed for delay data development was collected from 14 morning and evening KTM Komuter Monday and Friday trips on the SP-PB route from week two to four of February 2016. Delay data development in this study has used the original commuter schedule and primary data. As a result, the MIP run in Microsoft Excel has successfully achieved the minimum delay time of 1 minute and 45 seconds.